THE LOCAL WISDOM IN JAVANESE THINKING CULTURE WITHIN HANACARAKA PHILOSOPHY - Sari, Fitriana Kartika (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2020)
Abstract(Title: The Local Wisdom In Javanese Thinking Culture Within Hanacaraka Philosophy). Hanacaraka refers to the written language of Javanese, Javanese script. The name is based on the order of the twenty-Javanese-script, which is started by the series of hanacaraka script. This study aims to describe the local wisdom content of Javanese Thinking culture within the philosophical meaning of hanacaraka. This study used a semiotic approach applied to the main data source, namely Síªrat Kérata Basa. The results showed that (1) the philosophical meaning of the hanacaraka script was fully equipped with the wisdom of Javanese thinking culture in the form of symbolism and othak-athik mathuk which is supported by deep contemplation which involves all the common senses, including the inner sensitivity; (2) hanacaraka philosophy depicts God creature's (human) circumstances, which is equipped with creation, feeling, and effort; human cannot avoid all God's fate upon them until the end of their life; human conditions that achieve life harmony due to the ability to unify the manifestation of God and human characteristics, which heats up within themselves; human condition which put God's order highly by doing all the orders and avoiding all of His warnings. Keywords: local wisdom, Javanese thinking, Hanacaraka